Rationale, Methods, Feasibility, and Preliminary Outcomes of a Transdiagnostic Prevention Program for At-Risk College Students - Burke, Anne S.; Shapero, Benjamin G.; Pelletier-Baldelli, Andrea; Deng, Wisteria Y.; Nyer, Maren B.; Leathem, Logan; Namey, Leah; Landa, Carrie; Cather, Corinne; Holt, Daphne J. (Frontiers in Psychiatry, 2020)
Purpose Early adulthood represents one period of increased risk for the emergence of a serious mental illness. The college campus provides a unique opportunity to assess and monitor individuals in this at-risk age group. However, there are no validated early detection programs that are widely implemented on college campuses. In an effort to address this gap, we designed and tested an early detection and prevention program tailored to college students. A transdiagnostic approach was employed because of evidence for shared risk factors across major mental illnesses. Design Single arm, prospective study evaluating outcomes following a 4-week intervention. Method Three in-person mental health screenings were conducted on the campus of one university. Undergraduate students with at least mildly elevated, self-reported levels of depressive or subclinical psychotic symptoms, who were not receiving treatment for these symptoms, were invited to participate in a 4-session workshop focused on increasing self- and other- awareness and emotion regulation using established mindfulness, self-compassion, and mentalization principles and experiential exercises. Symptoms, resilience-promoting capacities, and aspects of social functioning were assessed pre- and post- intervention. Results 416 students were screened and a total of 63 students participated in the workshop. 91% attended at least 3 of the 4 sessions. The majority of participants found the workshop interesting and useful and would recommend it to a friend. Significant pre-to-post reductions in symptoms (depression, anxiety, and subclinical psychotic symptoms, ps < 0.004) and improvements in resilience-promoting capacities (self-compassion and self-efficacy, ps < 0.006) and indices of social functioning (social motivation, activity, and a measure of comfort with the physical presence of others, ps < 0.04) were observed. Moreover, the significant increases in resilience-promoting capacities correlated with the reductions in affective symptoms (ps < 0.03). Conclusions These findings suggest that an on-campus mental health screening and early intervention program is feasible, acceptable, and may be associated with improvements in resilience-related capacities and symptom reductions in young adults with non-impairing, subclinical symptoms of psychopathology. Follow-up work will determine whether this program can improve both shorter and longer-term mental health and functional outcomes in this at-risk population.